Effect of acceptor Na1+ doping on the properties of perovskite SrCeO3 - Yadav D.; Kumar U.; Nirala G.; Mall A.K.; Upadhyay S. (My University, 2025)
The aim of this work is to study the effect of Na doping on the structural, microstructural and electrical properties of SrCeO3. With this goal, SrCe1−xNaxO3 (x = 0, 0.02, 0.04, 0.06 and 0.10) polycrystalline ceramics have been prepared using the solid-state route. The phase and structure of the synthesized samples were confirmed using X-ray diffraction technique. Rietveld refinement of the XRD profile confirmed that all the samples have orthorhombic structure and space group Pnma. Further, the purity of the synthesized samples was checked using Raman and Fourier transformation infrared (FTIR) spectroscopy techniques. The optical bandgap was calculated using UV–Vis technique, and the values were found 3.01 and 3.12 eV for pristine and Na doped samples. Scanning electron microscopic studies of fractured surfaces of the sintered pellets have indicated that dopant Na has played a significant role in grain growth. Grain size and morphology of Na doped samples is different from pristine SrCeO3. DC conductivity of Na doped samples is lower than undoped SrCeO3. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.